Edukasi Gizi Isi Piringku Anak Sekolah SD 07 Kramat Pela Jakarta Selatan - Rosmida M. Marbun; Meilinasari; Anastu Regita Nareswara; Ratih Puspitaningtyas Purbaningrum; Ani Noviani (CV. Multi Kreasi Media, 2025)
The problem of nutritional imbalance in school-aged children remains a serious concern in Indonesia. Based on the 2023 Indonesian Health Survey (SKI), only 6.6% of children aged 5–12 years consumed the recommended amount of fruits and vegetables. Education about balanced nutrition through visual approaches such as